Lek and the dogs - Naylor, Hattie; Finer, Jem 1955- (Home Artist Film, 2018)
"Award winning artist and filmmaker Andrew Kotting adapts Hattie Naylor's curriculum, award-winning play, Ivan and the Dogs, for cinema. Based on the extraordinary true story of Ivan Mishukov, who walked out of his Moscow apartment at the age of four and spent two years living on the city streets where he was adopted by a pack of wild dogs. [...]" [imdb.com]
Original: Großbritannien 2017
Special features: In addition to the full feature film, this Blu-ray includes a series of short films and an exclusive booklet with writing by Mark Kermode and Iain Sinclair.
Keywords: Film; Blu-Ray-Disc